Transcending Area Studies: Piecing Together the Cross-Regional Networks of Ibadi Islam - Ghazal, Amal N. (Comparative Studies of South Asia, Africa and the Middle East, 2014)
The area studies model is an impediment to the historical analysis of linkages and connections not governed by its geographical and conceptual boundaries. Its shortcomings are even more pronounced in the historiography of the modern period, when interactions and exchanges between different communities have changed dramatically, in both scale and scope. In the region loosely defined as the Middle East, the problem is further compounded by the collapse of the Ottoman order and the erection of state borders. The framework of methodological nationalism tied to those borders has been productive of certain kinds of histories and not others. In this intervention, Ghazal takes the case of Ibadis, their geographic distribution, political activism, and patterns of communication, to showcase the shortcomings of area studies as a model of historical analysis. A more viable alternative to spatially bounded analytical frames, Ghazal proposes, is the network.
Keywords: Réformisme

al-Nukhba al-ʿUmāniyya fī Zinjibār: Qirā’a fī Maṣādir wa-Uṭur al-Fikr al-Qawmī - Ghazal, Amal N. (al-Mu’tamar al-Duwalī : al-Dawr al-ʿUmānī fī ‘l-Sharq al-Ifrīqī, 11-13 Dec. 2012. Buḥūth al-Mu’tamar, 2014)

An Ottoman Pasha and the End of Empire: Sulayman al-Baruni and the Networks of Islamic Reform - Ghazal, Amal N. (Global Muslims in the Age of Steam and Print, 2014)
Keywords: Bārūnī; Sulaymān al- (1870-1940); Réformisme